Modernidad religión y discurso político en América Latina. (2016)
Interventions of seven Latin American politicians in debates about marriage of same-sex couples and abortion in the political system and the political public sphere, make it possible to analyze the nature and potential scope of the most important arguments in public discourse. The cases studied here are representative of the tensions between religion and political modernity in Latin America: on the one hand there is an instrumental use of religious language, and on the other hand there is a translation of moral values and religious beliefs into a secular language that can be understood and perchance shared by all citizens.